Pre-Transfer Circulating Progesterone and Clinical Pregnancy in HRT-FET Cycles - Kong Pham; Vinh Tran (Indonesian Journal of Obstetrics and Gynecology, 2026)
AbstractObjectives: To investigate the association between circulating progesterone concentrations measured one day prior to Frozen Embryo Transfer (FET) in Hormone Replacement Therapy (HRT) cycles and clinical pregnancy outcomes, and to determine the optimal progesterone threshold for predicting clinical pregnancy.Methods: A prospective cohort study was conducted at Da Nang Women and Children's Hospital from January 2023 to October 2024. A total of 243 women undergoing HRT-FET cycles were enrolled. Eligible participants had a body mass index (BMI) ≤25 kg/m², were aged 18–45 years, had an endometrial thickness >7 mm, and underwent transfer of one or two high-quality blastocysts. Circulating progesterone concentrations were measured on the fourth day of progesterone supplementation, one day prior to embryo transfer, and categorized into quartiles. Clinical pregnancy was defined by ultrasound confirmation of fetal cardiac activity at 7 weeks of gestation. Statistical analyses included t-tests, chi-square tests, multivariate regression, and receiver operating characteristic (ROC) curve analysis.Results: Clinical pregnancy rates across increasing progesterone quartiles were 31.7% (<9.1 ng/mL), 49.2% (9.1–<11.0 ng/mL), 50.8% (11.0–<13.5 ng/mL), and 57.4% (≥13.5 ng/mL). Women with progesterone concentrations <9.1 ng/mL had a significantly lower clinical pregnancy rate compared with those in higher quartiles (31.7% vs. 52.5%, p = 0.033). ROC analysis demonstrated moderate predictive performance (AUC 0.65; 95% CI: 0.58–0.72), with an optimal progesterone cut-off value of 10.35 ng/mL (sensitivity 80.9%, specificity 52.3%).Conclusions: Lower serum progesterone concentrations measured one day prior to embryo transfer are associated with reduced clinical pregnancy rates in HRT-FET cycles, supporting the clinical value of progesterone monitoring. However, given the single-centre design and moderate predictive performance, the proposed threshold should be interpreted with caution and validated in larger, more diverse populations.Keywords: clinical pregnancy, frozen embryo transfer, hormone replacement therapy, progesterone.